Combination of photothermal and photodynamic inactivation of cancer cells through surface plasmon resonance of a gold nanoring. (16th February 2016) - Chu, Chih-Ken; Tu, Yi-Chou; Hsiao, Jen-Hung; Yu, Jian-He; Yu, Chih-Kang; Chen, Shih-Yang; Tseng, Po-Hao; Chen, Shuai; Kiang, Yean-Woei; Yang, C C
Abstract: We demonstrate effective inactivation of oral cancer cells SAS through a combination of photothermal therapy (PTT) and photodynamic therapy (PDT) effects based on localized surface plasmon resonance (LSPR) around 1064 nm in wavelength of a Au nanoring (NRI) under femtosecond (fs) laser illumination. The PTT effect is caused by the LSPR-enhanced absorption of the Au NRI. The PDT effect is generated by linking the Au NRI with the photosensitizer of sulfonated aluminum phthalocyanines (AlPcS) for producing singlet oxygen through the LSPR-enhanced two-photon absorption (TPA) excitation of AlPcS. The laser threshold intensity for cancer cell inactivation with the applied Au NRI linked with AlPcS is significantly lower when compared to that with the Au NRI not linked with AlPcS. The comparison of inactivation threshold intensity between the cases of fs and continuous laser illuminations at the same wavelength and with the same average power confirms the crucial factor of TPA under fs laser illumination for producing the PDT effect.